Busting the Resistance: Antimicrobial Activity of Plant-Infused Nanoemulsions against Neisseria gonorrhoeae - Deshanta Naicker; Rowen Govender; Nathlee S. Abbai (International Journal of Microbiology)
The escalating antibiotic resistance rates in Neisseria gonorrhoeae (N. gonorrhoeae) are now a grave concern. There is a critical need for alternative treatment options for infection since N. gonorrhoeae has developed resistance to multiple antibiotics used for treatment. In this study, plant nanoemulsions from Ocimum tenuiflorum, Moringa oleifera, and Azadirachta indica were tested for their antimicrobial properties against N. gonorrhoeae. The study also assessed the toxicity of these plant nanoemulsions using human erythrocytes. The plants were sourced from the Botanical Gardens in Durban, South Africa. Nanoemulsions were produced from the dried plants using established methods. The nanoemulsion-based plant extracts were tested against laboratory (World Health Organization (WHO) strains) and clinical isolates of N. gonorrhoeae using the disk diffusion method. All six isolates had zones of inhibition for the 1000 μM concentration for all three nanoemulsion-based plant extracts. No zones of inhibition were observed for 100 μM, 10 μM, and 1 μM nanoemulsion concentrations for five of the isolates. Isolate G176 had zones of inhibition at 1000 μM and 100 μM concentrations for the nanoemulsions of Ocimum tenuiflorum. Both the WHO strains had zones of inhibition appearing at the 1000 μM concentration. For the WHO Y strain, zones of inhibition for both 1000 μM and 100 μM concentrations were observed for the nanoemulsions of Ocimum tenuiflorum and Azadirachta indica. According to the analysis, there was 0% haemolytic activity observed which suggests the nontoxic nature of the extracts. This study showed that the nanoemulsion and plant mix may potentially be used as a safer alternative to treat gonorrhoea.